Towards Well-being: What Are the Effects of the Sensory Garden on ‘Apparently Well’ People and Could It Be a Viable Self-help Tool for Staff and Students on Campus? - Souter-Brown, Gayle (Auckland University of Technology, 2020)
In New Zealand, chronic stress impacts staff and student well-being, productivity, relationships and behaviour. Stress recovery and attention restoration theories assert a need for nature connection. Internationally, many mental health treatment programmes are now nature-based. The Swedish University of Agricultural Sciences Alnarp, developed an evidence-based rehabilitation garden on campus as part of a horticulture therapy programme to treat people referred for burnout and depression. In UK, South Africa and Australia, hospitals and other health-related facilities use sensory gardens, which include texture, colour and fragrance, to promote well-being. While such sensory and therapeutic settings effectively reduce stress, they require the expense of a trained professional to facilitate the experience. Referencing sensory and therapeutic gardens, this research sought to understand whether salutogenic design of an unfacilitated place for nature connection is an effective stress-reducing health promotion tool for ‘apparently well’ people in a workplace setting. The multidisciplinary investigation incorporated health, landscape design and ecology to compare a biodiverse, wildlife-attracting sensory garden (SG) with ubiquitous urban open space (Awataha Plaza (AP)), at a University campus in Auckland, New Zealand. The mixed methods research comprised two studies. A randomised controlled trial (Study 1) enriched by qualitative data tested effects of environmental design on salivary cortisol and indicators of well-being. ‘Apparently well’ (n = 179) 18-65-year-old staff and students were randomised into two intervention groups, SG (n=60) or AP (n=60), and a control. Participants had a monitored ‘appointment with nature’ for 30 minutes once weekly for four weeks. The control group participated in data collection only. Study 2 tested the sustainability of the garden as a self-care tool. All participants could access the SG for 30 minutes once weekly for four weeks. Participants were tested pre and post intervention and monitored in the field. SPSS was used to analyse laboratory and survey data and generate generalised linear models. Themes were induced through Thematic Analysis. Study 1 showed positive effects of time spent in the SG and trends towards negative effects of the AP. Significant differences were observed in the Garden group post intervention in cortisol -16.1% (95% CI: -32.0%, 0.2%; p = 0.04), well-being 6.9% (95% CI: 2.7%, 11.1%) and productivity 2.8% (95% CI: 0.1%, 5.5%, p < 0.05). Similarly, participants perceived improved social connection, improved cognitive function, felt more in control, ate more healthily and exercised more in their leisure time. In Study 2, participants previously assigned to the garden group in Study 1 showed significantly higher voluntary attendance rates (90%) than participants originally assigned to the Plaza (84%) or Control (83%) groups (P < 0.05). This study suggests that ecological health is linked with human well-being. Spending time in a salutogenically-designed environment protects against stress and promotes well-being in a way that simply being outdoors or taking time out in a planted plaza does not. Participants valued the accessibility of the self-care environment. A positive effect was seen regardless of age, sex and culture. The university provided an effective setting for health promotion, with the sensory garden supporting staff and students towards well-being.
Keywords: Restorative environments; Salutogenic design; Workplace wellbeing; Mental health; Productivity; Landscape architecture; Biodiversity